Critical BEOL Aspects of the Fabrication of a Thermally-Assisted MRAM Device. (9th September 2015) - O'Sullivan, E. J.; Edelstein, Daniel; Marchack, Nathan; Lofaro, Michael; Gaidis, Michael; Joseph, Eric; Annunziata, Anthony; Pfeiffer, Dirk; Trouilloud, P. L.; Zhu, Yu; Holmes, Steve; Galan, Armand; et al.
Abstract : Recent developments in new switching methods, such as spin transfer torque and temperature-assisted switching (TAS), have greatly increased interest in MRAM. However, MRAM fabrication is challenging due to the lack of magnetic materials processing experience by semiconductor lines. In this talk, we will discuss key BEOL fabrication aspects for a CMOS-integrated TAS MRAM on 200 mm wafers with, e.g., opens/shorts yields of 100% and 99% for 1 Mb and 16 Mb arrays, resp. This was achieved in our R&D line through careful process optimization and adherence to good BEOL processing.